2001
DOI: 10.1074/jbc.m107698200
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAP Kinase Mediates Nitric Oxide-induced Apoptosis of Neural Progenitor Cells

Abstract: Neural progenitor cells (NPC) can proliferate, differentiate into neurons or glial cells, or undergo a form of programmed cell death called apoptosis. Although death of NPC occurs during development of the nervous system and in the adult, the underlying mechanisms are unknown. Here we show that nitric oxide (NO) can induce death of C17.2 NPC by a mechanism requiring activation of p38 MAP kinase, poly(ADP-ribose) polymerase, and caspase-3. Nitric oxide causes release of cytochrome c from mitochondria, and Bcl-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 106 publications
11
81
4
Order By: Relevance
“…Many reports suggested that JNK or p38 MAPK induces apoptosis by regulating the translocation of Bax from the cytoplasm to the mitochondria in response to various stimuli (12)(13)(14). These results are consistent with the fact that JNK and/ or p38 MAPK acts at early step before dysfunction of mitochondria and caspase activation in several cell types (15)(16)(17). In contrast, recent observations showed that p38 MAPK is a critical regulator of cell survival and proliferation in response to cisplatin, camptothecin, doxorubicin, UV irradiation, and repetitive low-grade oxidative stress (18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Many reports suggested that JNK or p38 MAPK induces apoptosis by regulating the translocation of Bax from the cytoplasm to the mitochondria in response to various stimuli (12)(13)(14). These results are consistent with the fact that JNK and/ or p38 MAPK acts at early step before dysfunction of mitochondria and caspase activation in several cell types (15)(16)(17). In contrast, recent observations showed that p38 MAPK is a critical regulator of cell survival and proliferation in response to cisplatin, camptothecin, doxorubicin, UV irradiation, and repetitive low-grade oxidative stress (18)(19)(20).…”
Section: Introductionsupporting
confidence: 79%
“…Many reports suggested that p38 MAPK induces apoptotic cell death in response to various stimuli (15)(16)(17). In contrast, in this study we showed that p38 MAPK played a role in cell survival response against radiation-induced mitochondrial cell death.…”
Section: Discussioncontrasting
confidence: 51%
“…Caspase family members are key elements of programmed cell death in the developing nervous system [26], where this form of cell death affects both NPCs and postmitotic neurons. Activation of caspase-3 is required for embryonic and perinatal apoptosis of NPCs [21], which is inhibited by Bcl-2 [12]. In addition, in vitro studies show that caspase-3 is activated in NPCs undergoing neurotoxin-induced death in the adult brain [10].…”
Section: Discussionmentioning
confidence: 99%
“…Both JNK and p38 have been reported to mediate apoptosis in neural lineage cells. Nitric oxide induced apoptosis through p38 activation in neural progenitor cells (Cheng et al, 2001), whereas nutrient deprivation induced apoptosis through JNK activation in neurons. (Harris and Johnson, 2001).…”
Section: Discussionmentioning
confidence: 99%